Tilt - Hopkins, Ellen (New York : Margaret K. McElderry Books, 2012)
Three teens, connected by their parents' bad choices, tell in their own voices of their lives and loves as Shane finds his first boyfriend, Mikayla discovers that love can be pushed too far, and Harley loses herself in her quest for new experiences.
HL 590
Keywords: Dating (Social customs) -- Juvenile fiction; Love stories -- Juvenile fiction; Family problems -- Juvenile fiction; Family life -- Nevada -- Juvenile fiction; Novels in verse; Nevada -- Juvenile fiction